What do young adults on the edges of homeownership look like in big cities in an emerging economy: Evidence from Shanghai. (August 2017) - Chen, Jie; Yang, Zan
The characteristics of young households positioned on the edges of homeownership in a rapidly growing economy are investigated. This empirical work is based on a unique survey conducted in 2011 in Shanghai, which enables us to determine how young renters assess their major financial obstacles to becoming homeowners. We distinguish whether young renters attempting to access homeownership are constrained by a lack of sufficient funds for a down-payment, or by inadequate income, or by both. By connecting young renters' individual characteristics to the various financial constraints they face, we are able to characterise the renters who are situated on the edges of homeownership. Based on these findings, we make policy recommendations on how the government could improve the homeownership prospects of young households close to the boundary between renting and owning in urban China, as opposed to those with minimal chances of attaining homeownership.